Caracterização do perfil de ativação endotelial e disfunção plaquetária na doença renal crônica em pacientes pediátricos - Rivia Mara Morais e Silva (2016)
Chronic kidney disease (CKD) is associated with high morbidity and mortality, including hemostatic changes and cardiovascular diseases, and compromised patients' quality of life. In childhood, these changes are extremely relevant because they affect not only the course of the disease but also triggering impairments in adult life. The objective of the present study was to investigate the endothelial and platelet functions in pediatric patients with pre-dialytic CKD and compare it with healthy individuals, as well as to evaluate if the biomarkers analyzed were related to chronic kidney disease in children and adolescents. The study included 95 participants, 43 pediatric patients with chronic renal disease (CKD) in stages 1 to 4 on conservative treatment, and 52 healthy children (control group) matched for age and sex. Platelet activation markers expression: Pselectin platelet (CD62P), GPIIb/IIIa (CD41a), GPIIIa (CD61) and CD40L (CD154), and the percentage of platelet-leukocyte aggregates were determined by flow cytometry. Plasma levels of the endothelial activation biomarkers sEselectin, vascular endothelial growth factor (VEGF), vascular cell adhesion molecules (sVCAM-1) and intercellular (sICAM-1), uPA receptor biomarkers soluble (suPAR), ADAMTS13 and FVW were determined by ELISA. Expressions of P-selectin and GPIIIa in patients with CKD were lower than the control group. The percentage of platelet-monocyte aggregates, plasma levels of sE-selectin, VEGF, sICAM-1, sVCAM-1, suPAR, FVW and the FVW: ADAMTS13 ratio were higher in the disease. The levels of VWF and sE-selectin were reduced in patients treated with the Renin-Angiotensin Systems antagonists, reflecting an endothelial protection conferred by these drugs. The results allow to conclude that there was evidence of platelet dysfunction and endothelial activation in pre-dialytic CKD children and adolescents; the alterations are present early in the pediatric population and was promoted by renal disease; the changes in of platelet and endothelial biomarkers function and the levels of VWF and ADAMTS13 in CKD children and adolescents in pre-dialytic stages support the existence of a hypercoagulable state in these patients; the etiology of CKD (congenital malformations, glomerulopathies or others) showed no association with alteration of hemostatic biomarkers, platelet and endothelial dysfunction; there was a correlation between the expression of the platelet biomarkers and also between the production of endothelial activation markers. Reduction of RFG was associated with lower expression of platelet receptors, higher APM formation, and higher levels of endothelial markers. The biomarkers of platelet and endothelial activation, when assessed together by logistic regression, showed a relationship with CKD and with RFG.